B. Ed. First Year Students’ Motives for Learning English - Sharma, Lok Raj (International Research Journal of MMC, 2021)
This research article attempts to evaluate B.Ed. first year students’ major motives for learning English A cross-sectional survey design was adopted to accomplish the research study. The twelve questions as a data collection tool were administered to the students across three campuses of Makawanpur District, Nepal in the Academic Year 2019-2020. The study showed that a large number of the students learnt English to have good job opportunities in the country, whereas the smallest number of students learnt it to be tourist guides. The chi-square tests showed that there was statistically significant association between sex and the motives for learning it, whereas there was no statistically significant association between campuses and motives for learning it. The findings of the research study indicated that students learnt English for fulfilling differing purposes in their life. Their attitude towards learning English was found to be dissimilar.